2017
DOI: 10.12659/msm.901868
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lavage Techniques for Preventing Incision Infection Following Posterior Lumbar Interbody Fusion

Abstract: BackgroundThe main purpose of this study was to compare the effects of various lavage techniques – traditional saline lavage (SL), pulse lavage (PL), closed drainage (CD), and iodine lavage (IL) – on preventing incision-related infection after posterior lumbar interbody fusion.Material/MethodsPatients with prolapsed lumbar (intervertebral) discs (PLID) undergoing posterior lumbar interbody fusion surgery (PLIF) over the course of 2 years were included and were randomly allocated into 4 groups: the SL group, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In a prospective randomized trial on hip hemiarthroplasty for femoral neck fractures, a 2-liter PSL had a total infection rate of 5.5% compared to 15.6% for a 2-liter normal-saline gravity or bulb syringe lavage ( P = .002) [ 15 ]. Additionally, in 2 studies on spinal fusion surgeries, the infection rate of PSL vs bulb syringe lavage was 1.6% compared to 10.1% ( P = .046) and 2.5% compared to 20% ( P < .001) [ 13 , 14 ]. While efficacy data on the true ARR of PSL are sparse, what is available in the literature suggests that PSL is at least noninferior if not superior to historical lavage methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective randomized trial on hip hemiarthroplasty for femoral neck fractures, a 2-liter PSL had a total infection rate of 5.5% compared to 15.6% for a 2-liter normal-saline gravity or bulb syringe lavage ( P = .002) [ 15 ]. Additionally, in 2 studies on spinal fusion surgeries, the infection rate of PSL vs bulb syringe lavage was 1.6% compared to 10.1% ( P = .046) and 2.5% compared to 20% ( P < .001) [ 13 , 14 ]. While efficacy data on the true ARR of PSL are sparse, what is available in the literature suggests that PSL is at least noninferior if not superior to historical lavage methods.…”
Section: Discussionmentioning
confidence: 99%
“…One method for PJI prophylaxis that has been widely adopted is the pulsed lavage of 0.9% saline (PSL) [ 12 ]. Compared to the historical use of bulb syringe or gravity lavage, PSL has shown considerable efficacy in reducing surgical site infection rates across multiple surgical subspecialties [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. While the volume used in PSL varies depending on the anatomy of interest and surgeon preference, a few studies suggest 4 liters is optimal for TKA [ 20 , 21 ], but none have specific volume recommendations for PJI.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the flushing, patients were placed on the operating table in the best position, a sterile basin was kept below the wounds, and the table was covered with waterproof sheeting. The total volume of irrigating solution (0.9% physiological saline) depended on the situation of the wounds [ 23 ]. The volume generally was not less than 6000 mL for patients with severe burns.…”
Section: Methodsmentioning
confidence: 99%
“…Bath et al also found pulsed irrigation was more effective than bulb syringe irrigation in the posterior muscle layer [ 22 ]. Fei et al confirmed that a pulsed lavage group, closed drainage group, and iodine lavage group all showed much better postoperative infection prevention than the saline lavage group [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Studies have shown that the incisional infection rate among trauma surgery patients was 13.64%, with the percentage of Gram-positive and Gram-negative bacteria and fungi being 47.37%, 39.47%, and 13.16%, respectively. [5][6][7] Wound infections trigger the body's immune response, causing inflammation and tissue damage, while slowing the healing process. Many minor wound infections can heal spontaneously, such as localized infections after minor skin abrasions.…”
Section: Introductionmentioning
confidence: 99%